2019
DOI: 10.3390/f10070539
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Essential Oils of Chamaemelum fuscatum (Brot.) Vasc. from Spain as a Contribution to Reinforce Its Ethnobotanical Use

Abstract: Chamaemelum fuscatum (Brot.) Vasc. is a south west Iberian chamomile that has been traditionally used as folk medicine in its natural distribution area but currently it is underestimated regarding its biological activities. For this reason, it is proposed in this paper to get insight into the scientific validation of the traditional knowledge of this plant with the aim of taking advantage of its anti-inflammatory, gastroprotective and antinociceptive activities, among others. To this aim, the chemical composit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Afzelin), were isolated and identified in smaller proportions in the same study. In another study, Rasoanaivo et al [ 72 ] found higher trans-pinocarveol at 35.6–36.3% and pinocarvone at 19.8–20.0% in a species variety, Myrothamnus moschatus (Baillon) Niedenzu, endemic to Madagascar. The presence of 85 compounds, namely pinocarvone (11.13%), trans-pinocarveol (19.57%), limonene (6.09%), trans-p-menth-1-(7)-8-diene-2-ol (7.43% and cis-p-menth-1-(7)-8-diene-2-ol (6.76%), and others, representing 87.79% of the essential oil from hydro-distilled above-ground M. flabellifolius material, was reported [ 8 ].…”
Section: Phytochemical Composition Of Myrothamnus Flabellif...mentioning
confidence: 99%
See 1 more Smart Citation
“…Afzelin), were isolated and identified in smaller proportions in the same study. In another study, Rasoanaivo et al [ 72 ] found higher trans-pinocarveol at 35.6–36.3% and pinocarvone at 19.8–20.0% in a species variety, Myrothamnus moschatus (Baillon) Niedenzu, endemic to Madagascar. The presence of 85 compounds, namely pinocarvone (11.13%), trans-pinocarveol (19.57%), limonene (6.09%), trans-p-menth-1-(7)-8-diene-2-ol (7.43% and cis-p-menth-1-(7)-8-diene-2-ol (6.76%), and others, representing 87.79% of the essential oil from hydro-distilled above-ground M. flabellifolius material, was reported [ 8 ].…”
Section: Phytochemical Composition Of Myrothamnus Flabellif...mentioning
confidence: 99%
“…Myrothamus flabellifolius hydro-distillation produced 0.04% wet weight of essential oil [ 8 ]. Three-hour steam distillation of freshly collected aerial parts weighing 6 kg yielded 0.73% and 0.67% ( w / w ) essential oil from M. moschatus, commonly found in Madagascar [ 6 , 11 , 72 ]. Chaturvedi et al [ 11 ] found the following extract yields using different extraction methods: 14 (100% hexane), 32 (100% chloroform), 40 (100% methanol), 40 (70% methanol/water), and 48% (70% Ethanol/water) from sun-dried M. flabellifolius, collected in Botswana.…”
Section: Improving Bioavailability and Bioaccessibility Of Nutrients ...mentioning
confidence: 99%
“…On the other side, 2-methyl butyl isovalerate was the only identified oxygenated monoterpene, with a relative concentration of 10.43%. Isovalerate derivatives have been described in the EOs of several plants such as Eucalyptus brockwayii [37], Algerian Daucus gracilis [38], and Chamaemelum fuscatum [39]. Sesquiterpenes made up a relative concentration of 15.77% of the total oil mass.…”
Section: Chemical Composition Of P Lapathifolia Eomentioning
confidence: 99%
“…The beneficial potential of medicinal plants and herbs has been investigated in different papers [9][10][11][12]. Functionally, extracts and biologically active components [13][14][15][16][17][18] from forest products are experiencing great interest for both research and potential application in nutraceutical, pharmaceutical, and cosmetic fields [19,20]. Fernández-Cervantes et al [20] studied the essential oils of Chamaemelum fuscatum (Brot.)…”
mentioning
confidence: 99%